Illocutionary Acts Analysis in Donald Trump’s 2024 Victory Speech - Weny, Krisna (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
This study examined the speech acts of Donald Trump’s 2024 victory speech. The focus of speech acts studied by the researcher is illocutionary acts. The data was gathered by transcribing President-elect Donald Trump’s illocutionary acts from his victory speech into textual form. The data was analyzed qualitatively using John Rogers Searle’s theory of illocutionary acts, including declarations, directives, expressives, assertives, and commissives. The result of this study revealed that there were thirty-three utterances of illocutionary acts in Donald Trump’s 2024 victory speech. The most common acts were commissive, namely seventeen utterances, while directive acts were four of all illocutionary acts. Conversely, assertive acts were three utterances, and expressive acts were nine.